The effect of tacrolimus conversion from immediate- to extended-release formulation on renal function in renal transplant patients: a meta-analysis - Chao, Sheng; Jia, Lei; Zhu, Kejing; Chen, Luobei; Niu, Yulin (Frontiers in Pharmacology, 2023)
Objective: Tacrolimus formulation affects the outcomes of renal transplant, while the effect of its immediate-to extended-release conversion remains controversial. This meta-analysis aimed to compare the renal function before and after tacrolimus immediate-to extended-release conversion in renal transplant patients.Methods: PubMed, Cochrane, EMBASE, CNKI, CQVIP, and Wanfang databases were searched for articles regarding the effect of tacrolimus conversion from immediate-to extended-release formulation on renal function in renal transplant patients. The data of serum creatinine (Scr) or estimated glomerular filtration rate (eGFR) before and after conversion was extracted and analyzed.Results: Ten studies with 743 renal transplant patients were included. Scr was reduced after conversion versus before conversion [mean difference (MD) (95% confidence interval (CI)): -8.00 (-14.33; -1.66) μmol/L, P=0.01]. However, eGFR only showed an increased trend after conversion versus before conversion (MD (95% CI): 2.21 (-1.62, 6.03) mL/min/1.73m 2 , P=0.26), but without statistical significance. Furthermore, in patients with a follow-up duration ≥48 weeks, Scr was decreased after conversion versus before conversion (P=0.005), but eGFR remained unchanged (P=0.68); then, in patients with a follow-up duration <48 weeks, both Scr (P=0.36) and eGFR (P=0.24)were not different before conversion versus after conversion. Moreover, publication bias risk was low, and robustness assessed by sensitivity analysis was generally good.This meta-analysis favors studies indicating that the conversion of tacrolimus from an immediate-release to an extended-release formulation could